2022
DOI: 10.1080/21645515.2022.2045853
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 intranasal vaccines: current progress, advantages, prospects, and challenges

Abstract: Multiple vaccines have recently been developed, and almost all the countries are presently vaccinating their population to tackle the COVID-19 pandemic. Most of the COVID-19 vaccines in use are administered via intramuscular (IM) injection, eliciting protective humor and cellular immunity. COVID-19 intranasal (IN) vaccines are also being developed that have shown promising ability to induce a significant amount of antibody-mediated immune response and a robust cell-mediated immunity as well as hold the added a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 99 publications
1
61
0
5
Order By: Relevance
“…Data from mass vaccination efforts suggest that mRNA vaccines are safe, with adverse effects that are generally acceptable in frequency and severity. Nevertheless, rapid and robust local inflammation could be induced in mice‐administrated mRNA vaccines via intradermal, 91 intramuscular, 92 or intranasal routes 93 . This process was dependent on the ionizable lipid component of the LNP formulation 94 .…”
Section: Basics Of Mrna Vaccinesmentioning
confidence: 99%
“…Data from mass vaccination efforts suggest that mRNA vaccines are safe, with adverse effects that are generally acceptable in frequency and severity. Nevertheless, rapid and robust local inflammation could be induced in mice‐administrated mRNA vaccines via intradermal, 91 intramuscular, 92 or intranasal routes 93 . This process was dependent on the ionizable lipid component of the LNP formulation 94 .…”
Section: Basics Of Mrna Vaccinesmentioning
confidence: 99%
“…Moreover, a high-efficacy route of vaccine delivery and ease of administration should also be prioritized for vaccination. It has been proposed that the nasal vaccine holds promise for the next generation of anti-respiratory virus vaccines since it is close to the natural infection route [ 87 , 88 , 89 ]. Several studies have demonstrated that there are many advantages of using nasal or intranasal as a vaccine delivery path.…”
Section: Vaccine Approach To Prevent Infectionmentioning
confidence: 99%
“…Due to a lack of efficient therapeutic candidates, the world is having a difficult time battling this outbreak. Many research groups have developed COVID-19 vaccines such as mRNA vaccines, DNA vaccines, viral vector vaccines, virus-like particles (VLPs), recombinant vaccines, protein subunit-based vaccines, live attenuated and inactivated virus vaccines after a substantial amount of effort [ 2 , 3 ]. These vaccines are being employed to vaccinate people in various nations under national vaccination programs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%